Information System Public Administration Services Parianum Village, Muara Bengkal Sub-District - Amin Rais; Suswanto; Annafi Franz (Politeknik Pertanian Negeri Samarinda, 2022)
Seen from the population administration service in the village still uses a manual system for processing written data and archiving methods as data storage. Therefore, the purpose of this research is to provide better changes to community services by building an accurate and reliable registration and civil registration information system in parianum village, because in the application of community data storage is carried out directly from outlet services to databases by processing data through the website. Waterfall method or often called waterfall model provides a sequential or sequential software lifeline approach starting from analysis, design, coding, testing and supporting stages. Statistical Product and Service Solutions (SPSS) is an application used to perform advanced statistical analysis, data analysis with machine learning algorithms, string analysis, as well as big data analysis that can be integrated to build a data analysis platform. Pearson correlation or often called Correlation Product Moment is a statistical test tool used to test the associative hypothesis (relationship test) of two variables when the data is interval or ratio scale. The results of this study are easy to manage community data in Parianum village.